Asymmetric and shock effects of foreign AID on economic growth and employment generation - Abiola John Asaleye; Adeola Phillip Ojo; Opeyemi Eunice Olagunju (Research in Globalization, 2023)
The implications of foreign aid on economic growth and employment have been subjected to intense debate, with most studies focused on aggregated aid. However, different types of aid will probably affect growth and employment differently. Therefore, aggregating aid flows are most likely to provide ambiguous conclusions on their implication on employment and economic growth. The study investigates the asymmetric and shock effect of aggregated aid inflows and sectoral aid disbursement on growth and employment in Nigeria using a Non-linear Autoregressive Distributed Lags and Vector Error Correction Model. Evidence from the result shows that positive and negative shocks in aggregate aid increase and reduce growth in the long run, respectively, while negative shocks reduce growth in the short run. Likewise, positive shock reduces employment in the long run. And positive and negative shocks in aggregate aid reduce and promote employment, respectively, in the short run. However, the implications of the asymmetric effects of sectoral aid differ on growth and employment. The study reveals that positive shock in education and health aid increases employment in the long run, while positive shock in health and industry aid undermines growth in the short run. Also, positive shock in infrastructural aid decreases employment in the long run, while positive and negative shocks in infrastructural aid instigate employment in the short run. And these results confirm the asymmetricity of sectoral and aggregated aid on employment and growth. In addition, evidence from the variance decomposition tables shows that aggregated aid shock affects economic growth more than employment. Also, education and infrastructural aid affect economic growth more than employment. At the same time, health and industry aid affect employment more than economic growth. Based on the outcome of the findings, the study suggests the need to safeguard the aid inflow into the country and channel it to promote pro-growth in human capital formation to ensure long-term employment growth, especially education and health aid.
Keywords: 330; Aid; Asymmetric effects; Economic growth; Employment; Shock effects